The structure and behavioral effects of revealed social identity preferences - Florian Hett; Markus Kröll; Mario Mechtel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2019)
A large body of evidence shows that social identity affects behavior. However, our understanding of the substantial variation of these behavioral effects is still limited. We use a novel laboratory experiment to measure differences in preferences for social identities as a potential source of behavioral heterogeneity. Facing a trade-off between monetary payments and belonging to different groups, individuals are willing to forego significant earnings to avoid belonging to certain groups. We then show that individual differences in these foregone earnings correspond to the differences in discriminatory behavior towards these groups. Our results illustrate the importance of considering individual heterogeneity to fully understand the behavioral effects of social identity.
Keywords: C91; C92; D90; 330; Social Identity; Identification Preferences; Social Preferences; Outgroup Discrimination; Behavioral Heterogeneity; Social Status; Social Distance